The The Translation Procedures of Cultural Words in an Indonesian Phrasebook - Frihatmawati, Rizky; Rentiana, Leny Hikmah; Dhini, Ulfa Rahma (Indo-MathEdu Intellectuals Journal, 2023)
The research aimed to find out what kind of translation procedures were used in cultural words in an Indonesian Phrasebook, how they were applied, and the most dominant procedure used in the translation. The writer took the data from the Indonesian Phrasebook by Lonely Planet. This research employed qualitative method with content analysis technique. The writer concluded that the translator used four procedures in translating Indonesian cultural words. The translation procedures were descriptive equivalent, cultural equivalent, couplet, and naturalization. The most dominant translation procedure is descriptive equivalent, and the least is naturalization. The translator tended to use descriptive equivalence procedures in the translation to keep the cultural features of the source text complete in the target language, and the description provides further information about the cultural words for the readers